Novel Prosopis juliflora leaf ethanolic extract as natural antimicrobial agent against food spoiling microorganisms - Iman Saleh (14152878) (2022)
Fresh produces spoilage is a worldwide concern that accompany the global increase in food demand. Adverse human health and environmental effects of commercial spoilage control agents are major public concern. In this study, Prosopis juliflora leaves and fruit extracts had their antimicrobial activities evaluated against the growth of selected bacteria and yeast, and against mycelial growth and conidial germination of selected mycotoxins-producing fungi. P. juliflora water-soluble leaf ethanolic (PJ-WS-LE) extract with its novel extraction method showed the strongest antibacterial activity. Antimicrobial tests showed total inhibition of Botrytis cinerea, Alternaria alternata, Bacillus subtilis, Staphylococcus aureus and Candida albicans with MICs ranging between 0.125 and 1 mg/ml. Percent inhibition of mycelial growth (PIMG) of the extract was also determined against seven other fungal strains with highest value against Geotrichum candidum (66.2%). Even the least affected fungal strain showed alterations in their hyphae and spores exposed to PJ-WS-LE extract when observed using scanning electron microscope (SEM), alterations include exfoliated flakes, pores, vacuolation and applanation. Small-scale fruit bioassays controlled experiment showed high efficacy of the extract in protecting inoculated cherry tomato samples from B. cinerea and A. alternata infections. In conclusion, PJ-WS-LE extract is a feasible, natural antifungal agent that can replace common anti-spoiling chemicals. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-021-86509-3